The impact of lifestyle guidance intervention on health outcomes among Japanese middle-aged population with metabolic syndrome: A regression discontinuity study. (December 2022) - Li, Yunfei; Babazono, Akira; Jamal, Aziz; Liu, Ning; Fujita, Takako; Zhao, Rui; Maeno, Yukari; Su, Ya; Liang, Lifan; Yao, Lan
Abstract: Metabolic syndrome (MetS) prevalence has increased globally with considerable morbidity and economic burden at both individual and national levels. Japan is the first and only country that has introduced a nationwide lifestyle guidance intervention program to manage and control MetS. We conducted a quasi-experiment approach—regression discontinuity design—to evaluate the impact of this intervention on health outcomes at the population level. We retrospectively collected data of adults aged ≥35 years who participated in health checkups in 2015. Age in 2015 was used as the assignment variable, and an age of 40 years old was the threshold because those with MetS aged ≥40 were required to receive lifestyle guidance intervention. Among 26, 772 MetS adults, those who received the intervention had significant reductions in obesity measurements (bodyweight, waist circumference, and body mass index [BMI]) after 1 year of this intervention. Blood pressure was also significantly reduced in men after 1 year of undertaking the intervention. The results were similar when including demographic, socioeconomic, and behavioral covariates and using alternative functional forms to estimate the impact, or when bandwidths around intervention thresholds were changed. Our results showed that lifestyle guidance intervention for MetS has an important impact on weight loss and blood pressure reduction at the population level. This intervention could address the high burden of obesity and cardiovascular diseases in Japan and other countries with an unmet need for MetS prevention and management. Highlights: Japan has introduced a lifestyle guidance intervention program since 2008. This program targets middle-aged people with metabolic syndrome. This study evaluated the impact of this program at the population level. We applied a quasi-experiment approach, which may be less affected by confounders. Significant decreases in body weight and blood pressure were evident.